2018
DOI: 10.1097/md.0000000000012052
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptin in colorectal adenocarcinoma showed significant different survival patterns associated with tumor size, lymphovascular invasion, distant metastasis, local recurrence, and relapse of disease in the western province of Saudi Arabia

Abstract: Leptin phenotype has been suggested to be a possible biomarker for the diagnosis and prognosis of different neoplasms. Nonetheless, there are conflicts among the outcomes found in several tumors, and little is proven concerning the correlation between the phenotype of leptin and its clinical significance in colorectal carcinomas. This study will describe the phenotype of leptin in colorectal adenocarcinomas, and investigate its correlation with clinicopathological factors.Two hundred and twenty eight tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
(30 reference statements)
2
15
0
Order By: Relevance
“…However, previous findings regarding leptin expression and CRC risk have been conflicting. It could be due to sample size, diversity of populations, semiquantitative staining protocol, and procedure sensitivity [9]. To address these shortcomings, we obtained and analyzed the required data in the TCGA database and validated the results analyzed by a cohort with a relatively large sample size, which is a key strength of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous findings regarding leptin expression and CRC risk have been conflicting. It could be due to sample size, diversity of populations, semiquantitative staining protocol, and procedure sensitivity [9]. To address these shortcomings, we obtained and analyzed the required data in the TCGA database and validated the results analyzed by a cohort with a relatively large sample size, which is a key strength of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown the clinical significance of leptin in CRC [9][10][11][12][13][14], however, the results remained inconsistent. It might be due to a small sample size and different patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Mice with adipose MCP1 deficiency exhibited lower plasma concentrations of PAI1, leptin, and resistin, particularly those fed the HFD. PAI1 (34,35), leptin (36,37), and resistin (38,39) are proinflammatory cytokines with demonstrated cancer-promoting potential. Depletion of PAI1 inhibited spontaneous metastasis of LLC (33), knockout of leptin receptors mitigated mammary tumorigenesis mediated by mouse mammary tumor virus (40), and inhibition of resistin expression suppressed experimental metastasis of chondrosarcoma in mice (41).…”
Section: Discussionmentioning
confidence: 99%
“…But LEP concentration is the highest in moderately differentiated (G2) cancers compared to poorly differentiated (G3) cancers. Similarly, Al-Maghrabi et al(80) PeerJ reviewing PDF | (2019:05:37549:1:0:REVIEW 5 Jul 2019)…”
mentioning
confidence: 99%
“…Staining intensity has been given scores 0, 1, 2, and 3 demonstrating negative, faint, moderate, and strong staining respectively. For simplification of analysis, scores of staining intensity have been grouped as negative, low (1+) and high (2+ and 3+), as was reported previously(74,80) Statistical analysis SPSS software (version 22.0) was used for all statistical calculations. Spearman's rho coefficient was used to determine correlations between the variables.…”
mentioning
confidence: 99%